2021
DOI: 10.3390/jcm10194339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Outcomes and Sex-Related Disparities in Pneumonia: A Matched-Pair Analysis with Data from Spanish Hospitals (2016–2019)

Abstract: (1) Background: the purpose of this study is to analyze the incidence and in-hospital mortality (IHM) of community-acquired pneumonia (CAP) needing hospital admission and hospital-acquired pneumonia (HAP) in Spain (2016–2019). (2) Methods: using the Spanish Register of Specialized Care-Basic Minimum Database, we estimated the incidence of CAP and HAP. We matched each woman with a man with an identical age, according to comorbidities. (3) Results: we analyzed 518,838 cases of CAP and 38,705 cases of HAP, and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…[ 124 ] Retrospectiv, 2010–2014 Germany 19.200 cases of pneumonia from 127.000 nursing homes’ patients, all ≥ 65 years old Incidence rate: 20.9 (M) vs 9.6 (F) /100 person-years. HR for male sex = 1.88 (1.83–1.94) Not reported Pessoa et al [ 83 ] Retrospectiv, 2000–2014 Portugal 549.000 hospitalizations due to CAP M: F = 55: 45 Male sex is a risk factor for IHM: adjusted OR = 1.261 (95%CI 1.243–1.280) Peyrani et al [ 87 ] Secondary data analysis, 2014–2016 USA 7.449 patients with CAP Not reported No sex-related difference was found in groups with clinical improvement, clinical failure or non-resolving pneumonia Sun et al [ 14 ] Retrospectiv, 2016 China 1.48 million CAP episodes from 427 million patients Incidence rate: 7.32 (M) vs 6.93 (F) /1000 person-years; after standardizing for age: 9.52 (M) vs 8.54 (F) /1000 person-years Not reported de Miguel-Yanes et al [ 16 ] Retrospectiv, 2016–2019 Spain 519.000 patients with CAP M: F = 59: 41. Incidence rate: 429.59 (M) vs 283.3 (F) /100.000 inhabitants.…”
Section: Epidemiology and Etiology Of Cap: Does Sex And Gender Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 124 ] Retrospectiv, 2010–2014 Germany 19.200 cases of pneumonia from 127.000 nursing homes’ patients, all ≥ 65 years old Incidence rate: 20.9 (M) vs 9.6 (F) /100 person-years. HR for male sex = 1.88 (1.83–1.94) Not reported Pessoa et al [ 83 ] Retrospectiv, 2000–2014 Portugal 549.000 hospitalizations due to CAP M: F = 55: 45 Male sex is a risk factor for IHM: adjusted OR = 1.261 (95%CI 1.243–1.280) Peyrani et al [ 87 ] Secondary data analysis, 2014–2016 USA 7.449 patients with CAP Not reported No sex-related difference was found in groups with clinical improvement, clinical failure or non-resolving pneumonia Sun et al [ 14 ] Retrospectiv, 2016 China 1.48 million CAP episodes from 427 million patients Incidence rate: 7.32 (M) vs 6.93 (F) /1000 person-years; after standardizing for age: 9.52 (M) vs 8.54 (F) /1000 person-years Not reported de Miguel-Yanes et al [ 16 ] Retrospectiv, 2016–2019 Spain 519.000 patients with CAP M: F = 59: 41. Incidence rate: 429.59 (M) vs 283.3 (F) /100.000 inhabitants.…”
Section: Epidemiology and Etiology Of Cap: Does Sex And Gender Matter?mentioning
confidence: 99%
“…Moreover, sex-based differences were observed also for the prevalence of several comorbidities: while both sexes were frequently affected by metabolic disease (27.8% of males, 26.9% of females) and cardiovascular disease (20.5% of males and 15% of females), diabetes and smoking were mainly found in men (17.9% and 15.5%, respectively), while depression and anemia were more frequently found in women (20.0% and 15.8%, respectively) [ 13 ], although another study has found anemia to be more commonly reported in males [ 15 ]. A large Spanish cohort confirmed that men with CAP presented with overall more comorbidities, although with lower prevalence of heart failure (25.5% in women, 20.5% in men), dementia (11.3% vs 7.3%), and rheumatoid disease (3.7% vs 1.8%) [ 16 ]. Finally, type-2 diabetes mellitus (T2DM) [ 17 ] and COPD [ 18 ] were associated with a higher CAP incidence in both sexes, but disproportionally more in men than women.…”
Section: Epidemiology and Etiology Of Cap: Does Sex And Gender Matter?mentioning
confidence: 99%
“…Despite this, there is sparse evidence on how prevalent and incident AF modify IHM in people admitted for pneumonia. We believe that this study, along with previous research from our group [ 3 ], contributes to fill a gap in the medical literature, where the complex interaction between sex and the two common conditions of AF and pneumonia deserves further attention.…”
Section: Discussionmentioning
confidence: 68%
“…Important efforts have been made to reduce its morbimortality and associated health costs, and these have been mainly successful in the case of ventilator-associated pneumonia (VAP) [ 2 ]. However, VAP only represents a small fraction of all HAPs [ 3 ]. Some experts have claimed that there is a need to implement strategies to reduce the impact of not ventilator-associated HAP (NV-HAP), which continues to be an important cause of mortality even in fully developed countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation